2021
DOI: 10.3390/ijms22010458
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Oxygen Partial Pressures Induce a Distinct Transcriptional Response in Human PBMC: A Pilot Study on the “Normobaric Oxygen Paradox”

Abstract: The term “normobaric oxygen paradox” (NOP), describes the response to the return to normoxia after a hyperoxic event, sensed by tissues as oxygen shortage, and resulting in up-regulation of the Hypoxia-inducible factor 1α (HIF-1α) transcription factor activity. The molecular characteristics of this response have not been yet fully characterized. Herein, we report the activation time trend of oxygen-sensitive transcription factors in human peripheral blood mononuclear cells (PBMCs) obtained from healthy subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 51 publications
6
76
0
Order By: Relevance
“…Our study indicated that the exposure to mild hyperoxia, perceived as a hypoxic stress, is characterized by the activation of HIF-1α and NRF2, but not nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) in circulating PBMCs. In the same study, we also observed that, conversely, a temporary exposure to high hyperoxia leads to a progressive loss of NOP response in favor of features characterizing the presence of a frank oxidative stress associated to the activation of NRF2 and NF-κB and to glutathione synthesis, describing a hormetic adaption of antioxidant cellular defense [17]. These specific transcription factors are not only involved in the hormetic organism's response to oxidative stress, but also play a pivotal role in inflammation as they control the expression of specific mediators [27].…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…Our study indicated that the exposure to mild hyperoxia, perceived as a hypoxic stress, is characterized by the activation of HIF-1α and NRF2, but not nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) in circulating PBMCs. In the same study, we also observed that, conversely, a temporary exposure to high hyperoxia leads to a progressive loss of NOP response in favor of features characterizing the presence of a frank oxidative stress associated to the activation of NRF2 and NF-κB and to glutathione synthesis, describing a hormetic adaption of antioxidant cellular defense [17]. These specific transcription factors are not only involved in the hormetic organism's response to oxidative stress, but also play a pivotal role in inflammation as they control the expression of specific mediators [27].…”
Section: Discussionsupporting
confidence: 57%
“…This threshold of the oxygen effect can be explained by the fact that the expression of IL-6 is mainly regulated by the activation of NF-κB [46], which is dependent of oxygen levels. As mentioned above, we have already reported that while mild hyperoxia is associated to the activation of this transcription factor, higher oxygen concentrations induce a response pattern dominated by the activation of NRF2 with no evident upregulation of NF-κB activity [17].…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations